STRATEGI ORANG TUA DALAM MEMBIMBING REMAJA PUTUS SEKOLAH SMA DI KELURAHAN LAMPA BARAT (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
This paper aims to determine the Parents' Strategy in Guiding Adolescent High School Dropouts in Lampa Barat Village, Duampanua District, Pinrang Regency. The results showed that the method of Parents Strategy in Guiding Adolescent High School Dropouts in Lampa Barat Village, Duampanua District, Pinrang Regency by means of parents giving freedom of responsibility to adolescents, giving commendable advice, doing habituation, making parents as role models, involving youth in activities religion, and create a harmonious family. And the obstacles experienced by parents in guiding teenagers who drop out of high school in West Lampa Village are bad adolescents' association, the influence of social media, lack of intensity of meeting parents and adolescents, lack of willingness to go to school, lack of interest in learning, lack of empowerment activities. teenagers dropping out of school in the environment, as well as the inadequate economy, and the existence of early marriage.